Unscrambling Chaos Through Thick and Thin: An Explanation - Melese, Francois; Transue, William (Quarterly Journal of Economics, 1987)
Francois Melese, William Transue; Unscrambling Chaos through Thick and Thin: An Explanation, The Quarterly Journal of Economics, Volume 102, Issue 1, 1 Feb